joom | júm, n. (Oxford English Dictionary, 2023)
The increase in the number of injectable filler procedures has led to a rise in associated complications, with vascular compromise being the most feared. As a result, blood flow can be interrupted, leading to ischemia, necrosis or ulcerations, pulmonary embolism, blindness, and cerebral vascular injuries. In this context, Doppler high-frequency ultrasound (DHFUS) is a radiological tool that can be used to avoid, to diagnose, and to treat vascular complications. This study aims to review facial vessels anatomy and major variations, describe the examination technique, probe positions and teach how to recognize vascular occlusions, in order to avoid negative outcomes.